Ogniroth studios: Transforming ideas into innovation - Ahmed, J.U.; Uddin, M.J.; Shimul, Anwar Sadat; Huda, S.S.M.S. (2015)
© 2015 Birla Institute of Management Technology. The Ogniroth Studios has been an overwhelming experience in understanding how animation firms operate in Bangladesh, especially about their major promotional and marketing strategies, overall attitude and behaviour of the advertising industry towards animation and video effects (VFX). Ogniroth Studios is one of the leading VFX-based firms in Bangladeshi advertising industry that offers animation and VFX services to different clients. Since its inception, it has been dedicatedly exploring innovation and delivering outstanding and quality works. The advertising agencies that operate in Bangladesh are not equipped with in-house VFX facilities, and therefore they primarily rely on external firms, such as, Ogniroth Studios. Although such industry has a very short history in Bangladesh, over the past four years of operation Ogniroth Studios has successfully managed to offer outstanding works and thus satisfying the clients by being competitive to the global market. The founders of Ogniroth Studios believe in promoting innovation; thus, they do not restrict the boundary of imagination. Marketing activities and branding of Ogniroth Studios play a vital role to its achieving sustainability.